Nepetoidin B, a Natural Product, Inhibits LPS‐stimulated Nitric Oxide Production via Modulation of iNOS Mediated by NF‐κB/MKP‐5 Pathways. (15th May 2017) - Wu, Xiaxia; Gao, Hongwei; Sun, Wen; Yu, Jie; Hu, Hao; Xu, Qiongming; Chen, Xiuping
Abstract : Previous reports showed that nepetoidin B (NTB), a natural product isolated from many herbs, has anti‐fungal and anti‐bacterial effects. In this study, the antiinflammatory effect of NTB was investigated in lipopolysaccharide (LPS)‐stimulated RAW 264.7 macrophages. The cytotoxic effect of NTB and LPS was determined by MTT assay. The nitric oxide (NO) production was detected by Griess assay. The TNF‐α and IL‐6 levels were determined by enzyme‐linked immunosorbent assay kits. Protein expressions were tested by western blotting. The transcription activity of inducible nitric oxide synthase (iNOS) was detected by luciferase assay. Immunofluorescence assay was used to observe the visualization of NF‐κB/p65 nuclear translocation. NTB and LPS showed no obvious cytotoxic effect on RAW 264.7 cells. NTB remarkably inhibited LPS‐induced NO and TNF‐α secretion in a concentration‐dependent manner while showed no significant effect on IL‐6 secretion. NTB inhibited LPS‐induced iNOS protein expression and transcription activity without affecting cyclooxygenase‐2. Furthermore, NTB suppressed LPS‐stimulated NF‐κB/p65 phosphorylation and nuclear translocation. In addition, NTB significantly inhibited LPS‐induced phosphorylation of JNK1/2 and p38MAPK without affecting ERK1/2. LPS‐induced inhibition of mitogen‐activated protein kinase phosphatase‐5 (MKP‐5) was completely reversed by NTB. In conclusion, these results suggested that NTB inhibited LPS‐stimulated NO production possibly via modulation of iNOS mediated by MKP‐5/NF‐κB pathways in RAW 264.7 cells. Copyright © 2017 John Wiley & Sons, Ltd.